Czy filozof analityczny potrzebuje epistemicznej viagry? - Woleński, Jan (Filozofia Nauki, 2000)
The paper is a reply to Jan Czerniawski's paper „On epistemic impotence of analytical philosophy” (Filozofia Nauki 3-4/1998). Czerniawski argues that the analytic method consists either in arbitrary stipulations or in the appeal to linguistic intuitions. He claims that the latter are subjective and moreover they cannot help deciding objective problems, while the former are an arbitrary creation of truth. Hence, the analytic method has to be assisted by an intuitive insight into objective situations. However, Czerniawski forgets one quite elementary circumstance. For there is something else between linguistic intuitions and arbitrary terminological stipulations - namely precisation of intuitions. And this is what the analytic philosophers care for the most; those analytic philosophers who are logicians at the same time, in particular. According to the analytic philosophers philosophically relevant intuitive insight into objective situations is always achieved through language. Therefore, we do not need an epistemic viagra in the form of the extra-linguistic insight directly into the objective situation.